Do guidelines provide evidence-based guidance to health professionals on promoting developmentally appropriate chronic condition self-management in children? A systematic review. (December 2020) - Saxby, Nicole; Beggs, Sean; Kariyawasam, Nadish; Battersby, Malcolm; Lawn, Sharon
Objectives: To determine whether evidence-based practice guidelines promote developmentally appropriate chronic condition self-management for children with asthma, type 1 diabetes mellitus, and cystic fibrosis. Methods: Systematic review of clinical guidelines current as at 22 September 2017, including assessment of quality of each guideline using the iCAHE 'Guideline Quality Checklist', and mapping of the supporting evidence. Results: Fifteen guidelines were identified: asthma ( n =7) and type 1 diabetes mellitus ( n =7), CF ( n =1). Guideline quality was variable, and 11 different grading systems were used. In total, there were 28 recommendations promoting age/developmental considerations. Recommendations focused on: collaboration ( n =15), chronic condition self-management education ( n = 17), clinicians' skills ( n = 4); personalized action plans ( n =3), problem-solving ( n =2); and the assessment of children's chronic condition self-management needs ( n =3). Developmental transitions are highlighted as important time points in some guidelines: preschool ( n =2), and adolescence ( n =3). All guidelines encouraged triadic partnerships between children, adult caregivers and clinicians. Evidence supporting the developmental aspects of the guidelines' recommendations was poor; only 14 out of 57 journals listed as evidence were concordant. Discussion: Current guidelines articulate that developmentally appropriate chronic condition self-management is important; however, more work needs to be done to translate the concept into practical clinical tools.